Effects of onabotulinum toxin type A injections in patients with Meige's syndrome - Alexia Duarte; Léo Coutinho; Francisco Manoel Branco Germiniani; Hélio Afonso Ghizoni Teive (Arquivos de Neuro-Psiquiatria)
Background Meige's syndrome is a type of facial dystonia characterized by the simultaneous occurrence of blepharospasm and oromandibular dystonia. Although botulinum toxin type A (OBTA) injections are the standard treatment, evidence of their effectiveness and safety in this scenario is still lacking.